(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Even the most trivial thing can have a great impact on life, in both positive and negative way. Positive effects can always be welcomed as it changes the life of the receiver in a better way. But this is not the same in the case of negative impacts. It can affect them both physically and mentally.